2022
DOI: 10.1155/2022/6641904
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Upcycled Brewers’ Spent Grain on Consumer Acceptance and Predictors of Overall Liking in Muffins

Abstract: The brewing industry generates large amounts of food waste including brewers’ spent grain (BSG) and leftover malted grains from beer production. BSG compositions can vary but consistently include high levels of protein and fiber. The potential nutritional and health benefits of BSG have sparked recent interest for food fortification. However, the challenges associated with BSG addition can impact food quality due to increases in fiber and protein content and reduction in starch content. Consumer testing was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…Finally, the overall quality of breads was positively correlated with a malty smell (0.68) and crumb saltiness (0.70), and negatively correlated with ash and IDF% (−0.72 and −0.52), and with crumb fibrousness and porosity (−0.56 and −0.58). Our results were only partially in agreement with the findings of Ktenioudaki et al [16], who found that taste and texture were the attributes that mostly affected the overall acceptability, and with the results of Combest and Warren [74], who found significant correlations only between taste and overall liking. In fact, in our study, some smell, taste, and texture attributes are correlated with the overall sensory quality of breads.…”
Section: Principal Component Analysis and Pearson Coefficientssupporting
confidence: 91%
“…Finally, the overall quality of breads was positively correlated with a malty smell (0.68) and crumb saltiness (0.70), and negatively correlated with ash and IDF% (−0.72 and −0.52), and with crumb fibrousness and porosity (−0.56 and −0.58). Our results were only partially in agreement with the findings of Ktenioudaki et al [16], who found that taste and texture were the attributes that mostly affected the overall acceptability, and with the results of Combest and Warren [74], who found significant correlations only between taste and overall liking. In fact, in our study, some smell, taste, and texture attributes are correlated with the overall sensory quality of breads.…”
Section: Principal Component Analysis and Pearson Coefficientssupporting
confidence: 91%
“…The high fiber content helps in the elimination of cholesterol and fats and improves symptoms of ulcerative colitis [ 31 , 33 , 34 , 35 , 36 ]. Reusing spent grain as a value-added food source for human consumption is appealing because it increases the protein, fiber, vitamin and mineral contents while decreasing the starch and caloric content in grain-based products [ 40 ].…”
Section: Nutritive Value Of Spent Grainsmentioning
confidence: 99%
“…Another study on the use of spent grain in muffins found that 30% spent grain retains consumer approval and offers more chances of triggering biological reactions due to the higher levels of proteins, fiber and antioxidants. Furthermore, nutrient content could be mentioned on the labels of muffins with 20% and 30% spent grain, both of which are considered “good sources” of protein and fiber, because the portion size contains more than 10% of the recommended daily value of each nutrient [ 40 ].…”
Section: Possible Uses Of Spent Grain In Food Productsmentioning
confidence: 99%